INDUKSI TUNAS TIN (Ficus carica L.) SECARA IN VITRO - Nova Triani; Pangesti Nugrahani; Elly Syafriani (Plumula : Berkala Ilmiah Agroteknologi, 2018)
This work aimed to study the effect of (Benzyl Amino Purine) BAP and coconut water in Murashige and Skoog (MS) medium on shoot induction of shoot Fig. For this purpose, 1 ppm and 2 ppm of BAP and 100 ml/l and 150 ml/l of coconut water were in MS medium with or without carbon, were investigated. This research used Completely Randomized Design with 9 treatments, there are zero MS, MS+BAP 1 ppm, MS+BAP 2 ppm, MS+BAP 1 ppm+carbon, MS+BAP 2 ppm+carbon, MS+CW 100ml/l, MS+CW 150 ml/l, MS+CW 100 ml/l+carbon, and MS+CW 150 ml/l. Shoot of the Fig were cultured on those MS medium supplemented with 30 mg/l sugar for in vitro shootlet proliferation. It was found that MS medium supplemented with BAP 1 ppm+carbon, enhanced shoot development. In this study there were still many explants were died because of browning and contamination.